Strategi Pemasaran Dreyy Store Dalam Mempertahankan Penjualan di Era Persaingan Thrift Shop Melalui Instagram - Prasetyo Adinugroho; Meilyati Rohmah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Rapid technological developments have significantly impacted various sectors, including the fast-growing and highly competitive business industry in Indonesia, particularly in the thrift shop market. Dreyy Store, a thrift shop business in Bogor, employs a digital marketing strategy through Instagram to maintain sales and attract young consumers by offering quality imported second-hand clothing at affordable prices. This qualitative study uses in-depth interviews, observation, and documentation to analyze Dreyy Store’s marketing strategies based on the 4P marketing mix and SWOT analysis. Findings indicate that Dreyy Store successfully integrates quality products, competitive pricing, strategic location, and active social media promotion to maintain customer loyalty and market competitiveness. A primary obstacle identified is the limited human resources available for responsive social media customer service. The novelty of this research lies in its focus on integrating digital marketing strategies within a local thrift business, addressing specific industry challenges in Indonesia with innovative approaches.